Positive replication and linkage disequilibrium mapping of the Chromosome 21q22.1 malaria susceptibility locus - Khor, Chiea C. (2007)
Four cytokine receptor genes are located on Chr21q22.11, encoding the α and β subunits of the interferon alpha receptor (IFNAR1 and IFNAR2), the β subunit of the interleukin 10 receptor (IL10RB), and the second subunit of the interferon gamma receptor (IFNGR2). We previously reported that two variants in IFNAR1 were associated with susceptibility to malaria in Gambians. We now present an extensive fine-scale mapping of the associated region utilizing 45 additional genetic markers obtained from public databases and by sequencing a 44kb region in and around the IFNAR1 gene in 24 Gambian children (12 cases/ 12 controls). Within the IFNAR1 gene a newly studied C→G single nucleotide polymorphism (IFNAR1 272354c-g) at position −576 relative to the transcription start was found to be more strongly associated with susceptibility to severe malaria. Association was observed in three populations: in Gambian (P=0.002), Kenyan (P=0.022) and Vietnamese (P=0.005) case control studies. When all three studies were combined, using the Mantel-Haenszel test, the presence of IFNAR1 −576G was associated with a substantially elevated risk of severe malaria (N=2444, OR=1.38, 95%CI: 1.17-1.64; P=1.7×10(−4)). This study builds on previous work to further highlight the importance of the type I interferon pathway in malaria susceptibility and illustrates the utility of typing SNPs within regions of high linkage disequilibrium in multiple populations to confirm initial positive associations.